The French Royal Court and the Memory of the First Crusade - Naus, James L. (Nottingham Medieval Studies, 2011)
Abstract The powerful image of Louis IX on crusade has led scholars to argue that ‘royal French crusading’ was a tradition that developed only after Louis VII departed for the East in 1147. This article explores the formation of the earliest connection between the French royal house and the crusading movement in the first decade of the twelfth century. Key changes in the royal court transformed the body in the decade before the First Crusade as members of the lower aristocracy gradually began replacing the magnates. Philip I viewed these ‘new men’ in his court as his representatives on the expedition in 1095. However, when a majority of these men returned from the East before completing their vows, the royal court faced dangerous questions about its dynastic claims of divine favour. In response to this, several monks from northern France fashioned a version of the First Crusade that sanitized the careers of those knights in the royal entourage. It is this version of events that ultimately became the popular history of the First Crusade.